1996
DOI: 10.1182/blood.v87.7.2891.bloodjournal8772891
|View full text |Cite
|
Sign up to set email alerts
|

The 12;21 translocation involving TEL and deletion of the other TEL allele: two frequently associated alterations found in childhood acute lymphoblastic leukemia

Abstract: A recurrent t(12;21)(p13;q22) has recently been described in human acute lymphoblastic leukemias (ALLs). This translocation fuses TEL and AML1, two genes previously cloned from translocation breakpoints in myeloid leukemias. In addition, allelic loss of the TEL gene can be detected in 15% to 22% of childhood ALLs. In the present study, we have sought allelic deletions of TEL and the presence of the t(12;21) in 50 children with B-lineage ALL, using a combination of microsatellite typing, fluorescent in situ hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(85 citation statements)
references
References 11 publications
6
76
0
2
Order By: Relevance
“…We have previously described deletion of the 5¢ AML1 signal in a study using exon specific probes (Jabbar Al-Obaidi et al, 2002). This is further supported by molecular studies, which showed that the TEL/AML1 fusion RNA was present in all patients with t(12;21), whereas the reciprocal AML1/TEL transcript was found only in a subset of these patients (Raynaud et al, 1996) and by the fact that other significant chromosomal rearrangements are associated with deletions (Kolomietz et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
“…We have previously described deletion of the 5¢ AML1 signal in a study using exon specific probes (Jabbar Al-Obaidi et al, 2002). This is further supported by molecular studies, which showed that the TEL/AML1 fusion RNA was present in all patients with t(12;21), whereas the reciprocal AML1/TEL transcript was found only in a subset of these patients (Raynaud et al, 1996) and by the fact that other significant chromosomal rearrangements are associated with deletions (Kolomietz et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
“…In acute lymphoblastic leukaemia (ALL), the ETV6/AML1 rearrangement is often associated with a deletion of part or all of the second copy of the ETV6 gene (located at 12p13). A high proportion of cases have this deletion, indicating that it could be the event that precipitates the progression to acute leukaemia (Raynaud et al, 1996;Kempski et al, 1999;Douet-Guilbert et al, 2003). A deletion of ETV6 was not seen in the isolated, fusion positive cells identified in normal cord blood samples by fluorescence in situ hybridization (FISH), which supports this hypothesis (Mori et al, 2002).…”
mentioning
confidence: 74%
“…ETV6/AML1 fusion, however, appears to need a genetic 'second hit' for pathogenic transformation. Up to 88% of cases that are positive for ETV6/AML1 fusion have been shown to have a deletion of part or all of the second copy of the ETV6 gene at 12p13 (Raynaud et al, 1996;Kempski et al, 1999;Douet-Guilbert et al, 2003). Deletion of ETV6 is therefore an attractive candidate for this 'second hit', deemed to be essential for progression to overt leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The TEL±AML1:TBP ratio found for patient 12, whose blasts expressed only the TEL (exon 5)±AML1 (exon 3) fusion transcript, was 1´4, which did not differ from ratios found in patients displaying the usual breakpoint (Table II). Leukaemia blasts of patients 7, 11, and 15 showed chromosome 21 trisomy, which often leads to a der(21)t(12;21) duplication (Raynaud et al, 1996). However, no significantly higher TEL±AML1 expression was evidenced in these patients (Table II).…”
Section: Figmentioning
confidence: 93%
“…Although fusion transcripts are present only in 40% of childhood ALL, quantification of chimaeric messengers provides a useful alternative approach for MRD assessment because of its good sensitivity and because of the stability of such markers over time. The TEL±AML1 transcript, which is associated with t(12;21), is particularly interesting because it is found in 25% of childhood B-cell precursor ALL (Romana et al, 1995;Shurtleff et al, 1995;Raynaud et al, 1996;Borkhardt et al, 1997).…”
mentioning
confidence: 99%